Dampak Pandemi COVID-19 terhadap Pemanfaatan Pelayanan Kesehatan Maternal di Kabupaten Ngawi: Studi Rangkaian Berkala - Levi Nadilla Putri; Eny Qurniyawati; Dinda Ardanila; Ririh (Media Gizi Kesmas, 2024)
Background: The COVID-19 pandemic situation has had a serious impact on the maternal group (pregnancy, childbirth and postpartum women) in Indonesia. During 2021, the maternal mortality rate in Ngawi Regency will reach 276.9 per 100,000 live births after previously it was only 84.4 per 100,000 live births. The COVID-19 pandemic has become an directly and indirectly obstacle for mothers in accessing maternal health services. Objectives: This study aims to see whether there is an impact of the COVID-19 pandemic on differences in utilization of maternal health services in Ngawi District during May 2019 – April 2021. Methods: A quantitative-descriptive time-series research method was performed using data from Local Area Monitoring Reports-Maternal and Child Health in Ngawi Regency during 2019-2021. The data were analyzed univariately and using an independent t-test to check if there were any differences in the number of mothers who accessed health services before and during the pandemic. Results: There was a downward trend in the number of mothers receiving health services for each type of maternal health service in Ngawi District during May 2020 – April 2021. All types of maternal health services experienced an average decrease in the number of mothers receiving health services during the pandemic. Three of five maternal health services in this study which showed significant differences in the average number of mothers utilizing health services during the pandemic were antenatal care K4 (p = 0.001), healthcare deliveries (p = 0.045), and postpartum services (p = 0.031). Antenatal care K1 (p = 0.206) and management of obstetric complications (p = 0.131) did not show any significant differences statistically. Conclusions: Antenatal care K4, healthcare deliveries, and postpartum services experienced significant differences in the average number of mothers who utilized maternal health services before and during pandemic. The Regional Health Office, in collaboration with all healthcare providers, should develop a specific plans and strategies to facilitate better health care for those three maternal health services, particularly in pandemic situation..